Recent advances in the rare-earth metal triflates-catalyzed organic reactions - Wu, Yue-Hua; Zhang, Lei-Yang; Wang, Nai-Xing; Xing, Yalan (Catalysis reviews. Science and engineering, 2022)
In the past three decades, rare-earth metal triflates including scandium triflate, yttrium triflate, and the lanthanide (La−Lu) triflate, were widely employed in the organic chemistry, such as cyclization, C-H bond functionalization and types of reactions. Recently, the approaches using rare-earth metal triflates as catalysts have been mainly focusing on (1) achieving the high regioselectivity and stereoselectivity with effective ligands and (2) further extending the reaction scope by cooperation with other transition metal catalysts. This review mainly focuses on recent advances in the rare-earth metal triflates-catalyzed organic reactions from 2017 to 2019. This review also emphasis on reaction transformations and related mechanisms to show the general readership about capabilities, challenges as well as potential applications.